2022
DOI: 10.3390/dj10100181
|View full text |Cite
|
Sign up to set email alerts
|

Comparison in Terms of Accuracy between DLP and LCD Printing Technology for Dental Model Printing

Abstract: Background: The aim of this study is to evaluate the accuracy of a Liquid Crystal Display (LCD) 3D printer compared to a Direct Light Processing (DLP) 3D printer for dental model printing. Methods: Two different printers in terms of 3D printing technology were used in this study. One was a DLP 3D printer and one an LCD 3D printer. The accuracy of the printers was evaluated in terms of trueness and precision. Ten STL reference files were used for this study. For trueness, each STL file was printed once with eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 39 publications
1
11
1
Order By: Relevance
“…The DLP groups were more accurate than the LCD groups in terms of RMS, likely because of the difference in photopolymerization type rather than resolution. This was consistent with the findings by Tsolakis et al [ 32 ]. In shell-to-shell deviation, DLP printers were also more accurate, showing lower trueness values than LCD4s, suggesting that dimensional accuracy should be attributed more to the control of the photopolymerization by the printing principle rather than to the XY resolution of the 3D printers.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The DLP groups were more accurate than the LCD groups in terms of RMS, likely because of the difference in photopolymerization type rather than resolution. This was consistent with the findings by Tsolakis et al [ 32 ]. In shell-to-shell deviation, DLP printers were also more accurate, showing lower trueness values than LCD4s, suggesting that dimensional accuracy should be attributed more to the control of the photopolymerization by the printing principle rather than to the XY resolution of the 3D printers.…”
Section: Discussionsupporting
confidence: 94%
“…Joda et al studied the change of accuracy according to the storage period after printing and found that 1 day of aging resulted in the highest accuracy [ 29 ]. As such, several studies evaluated the accuracy of different 3D printers by physically measuring or scanning and superimposing printed models [ [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] ]. However, few studies made quantitative comparisons with numerical reference data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that entry-level LCD-based printers are less true and precise than professional-grade SLA printers. Tsolakis et al [ 49 ] compared the accuracy of DLP and LCD printing technologies for dental model printing, and their results suggested that DLP printers are more accurate than LCD printers in the case of dental model printing; however, both printers can accurately be used to print dental models for the fabrication of orthodontic appliances. Another study compared the accuracy of three different printing technologies [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…DLP printing technology is far superior in recreating details in parts than traditional FDM printing technology can achieve, and has been previously used to create phantoms for measuring dimensional accuracy in MRI scans 3,4 . DLP's ability to recreate details has been shown to be suitable in printing dental models demanding a high degree of accuracy 5,6 . Objects created by curing resin in such fashion is also inherently liquid tight 7,8 .…”
Section: Digital Light Processingmentioning
confidence: 99%